AB0125 Dendritic Cells Display Aberrant Toll-like Receptor Responses during The Onset of Systemic Lupus Erythematosus. (15th July 2016) - Yim, A.L.Y.; Yan, S.; Lee, C.C.P.; Lau, C.S.; Chan, V.S.F.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic, multifactorial autoimmune disease causing multi-organ damages (eg. kidney, heart and skin) and predominantly affects young female. The dysregulation of multiple immune cell populations leads to the development of SLE and the role of dendritic cells (DCs) in the disease pathogenesis has drawn great attention. Plasmacytoid DCs (pDCs) are potent type I interferon (IFN) producers and myeloid DCs (mDCs) are professional antigen-presenting cells. Clinically, the level of serum interferon alpha (IFNa) correlates with the severity of disease with pDC infiltration in nephritic kidney suggested that pDCs may contribute to SLE pathogenesis [1, 2]. Moreover, monocyte-derived mDCs from SLE patients also display activated phenotypes [3]. These findings suggested that different DC subtypes may contribute to the disease development but the exact mechanism is not fully understood. Objectives: This study aimed to investigate whether different DCs subtypes display any abnormalities during the onset of SLE and thus, contribute to SLE pathogenesis. Methods: Using the New Zealand Black /White F1 (BWF1) murine lupus model, the phenotypic and functional properties of different DCs subsets were compared before and after disease onset using flow cytometry, ELISA and qPCR. Results: Symptomatic mice had a lower frequency but similar number of splenic pDCs when compared with its pre-symptomatic counterparts. In terms of activation markers and co-stimulatory molecules, splenic pDCs from symptomatic and pre-symptomatic mice expressed similar levels of CD40, CD80 and MHC II upon Toll-like receptor (TLR) 7 or TLR9 stimulation. The levels of IFNa produced upon TLR9 stimulation were also comparable. For splenic mDCs, both the frequency and number were higher in symptomatic mice. Surprisingly, ex-vivo mDCs from symptomatic mice expressed lower levels of CD80 and MHC II but their ability in inducing allogenic T cell proliferation was comparable to mDCs from pre-symptomatic mice. On the other hand, the basal mRNA expressions of TLR7 and TLR9 on mDCs from symptomatic mice were higher. Upon TLR7 or TLR9 stimulation, the induction of IL-10 and CXCL13 mRNA in mDCs from symptomatic mice were also greater than its pre-symptomatic counterparts Conclusions: Results showed that mDCs displayed abnormality upon SLE onset and may contribute to SLE pathogenesis via aberrant TLR signalling. More work should be done to further investigate the exact role of mDCs in SLE pathogenesis. References: Dall'Era, M., et al., Type I interferon correlates with serological and clinical manifestations of SLE. Annals of the Rheumatic Diseases, 2005. 64(12): p. 1692–1697. Fiore, N., et al., Immature myeloid and plasmacytoid dendritic cells infiltrate renal tubulointerstitium in patients with lupus nephritis. Molecular Immunology, 2008. 45(1): p. 259–265. Ding, D., et al., Aberrant Phenotype and Function of Myeloid Dendritic Cells in Systemic Lupus Erythematosus. The Journal of Immunology, 2006. 177(9): p. 5878–5889. Acknowledgement: Hong Kong Research Grant Council General Research Fund (770213). Disclosure of Interest: None declared